Langganan Digital: Tinjauan Hukum Islam terhadap Perpanjangan Otomatis Aplikasi pada Generasi Z - Elsa Silvia Nur Aulia; Cecep Alba; Asep Wawan Jatnika; Sansan Ziaul Haq (Jurnal Sosioteknologi, 2026)
The rapid growth of digital subscription services has normalized auto-renewal mechanisms, particularly among Generation Z. However, this convenience often leads to passive consumption and unintentional financial deductions. This study aims to analyze the practice of autorenewal in digital subscriptions among Gen Z from both socio-technological and Islamic legal (fiqh muamalah) perspectives. Employing a quantitative descriptive approach, data were collected from 50 Gen Z respondents in Bandung through questionnaires. The findings reveal a high subscription rate (74%), yet a significant disconnect exists: 40% of users infrequently utilize the services they continue paying for, and 24% are unaware of active autorenewals. From a socio-technological view, platforms exploit user inertia, leading to a "subscribe-andforget" culture. In Islamic law, specifically within the 'aqd al-ijarah (service contract) framework, this practice raises critical issues regarding the absence of continuous ridha (mutual consent) and the presence of gharar (uncertainty). Paying for unutilized services directly violates the principle of 'adl (fairness). Interestingly, while 46% perceive the system as functionally unfair, 62% still view it as legally permissible (Halal/Mubah). Academically, this research contributes to contemporary Islamic jurisprudence by conceptualizing "algorithmic gharar" and redefining ridha as a continuous, dynamic requirement in automated digital contracts. However, as an exploratory baseline, the generalizability of this study is limited by its small, localized urban sample of 50 respondents, necessitating broader national studies. The study concludes there is an urgent need for enhanced digital financial literacy and ethical, transparent subscription designs.